Manajemen Penerapan Kurikulum 2013 di MTs AL-WASHLIYAH 30 Pematan Guntung Kecamatan Teluk Mengkudu Kabupaten Serdang Bedagai - Mayasari Mayasari; Mahanum Mahanum; Usiono Usiono (Edumaspul: Jurnal Pendidikan, 2021)
This research was conducted at MTs Al Washliyah 30 Pematang Guntung Teluk Mengkudu District, Serdang Bedagai Regency, this type of research is a qualitative research. As an informant in this study was the Deputy Head of the Madrasah curriculum section. Collecting data using the method of observation, interviews and documentation. Data analysis was carried out by means of data reduction, data presentation and conclusion drawing (verification). This study aims to: (1) To find out the management of the 2013 curriculum implementation. (2) To find out the obstacles experienced during the 2013 curriculum implementation. The results showed that (1) The 2013 curriculum implementation was carried out on the basis of Permendikbud No. 160 of 2014 concerning the implementation of the 2006 curriculum and the 2013 curriculum and implemented according to the technical guidelines of the Minister of Religion Decree No. 207 of 2014 concerning the structure of the implementation of the sympathetic madrasa curriculum. (2) Require all educators to complete administration such as syllabus, KKM, Semester Program (PROTA), Semester Program (PROSEM), Learning Device Plan (RPP), Assessment and others. (3) The steps taken in implementing the 2013 curriculum are following the technical guidelines of the Ministry of Religion, following the 2013 curriculum structure that is enforced based on the Permendikbud. (4) The obstacle experienced when implementing the 2013 curriculum in the madrasa is the lack of training for educators in implementing the 2013 curriculum.